Periodic Table of chemical elements and Soviet atomic project - R. E. Kusin (Тонкие химические технологии, 2019)
The Soviet atomic project, also known as the nuclear shield, is a true triumph of the Periodic Law. Unlike other global projects, it covers the entire Periodic Table of chemical elements: from the first element of the table (hydrogen) to the last one at the time of the project’s completion (plutonium). The article, based on rare open publications, describes the main stages and chemical-technological issues surrounding the creation of atomic and thermonuclear weapons - the main goal of the nuclear shield New fundamental results of the chemistry and technology of isotopes of hydrogen, lithium, beryllium, polonium, uranium, and plutonium have been obtained that could significantly expand the Periodic Table of chemical elements.